Creating digital promotional material for Coban Waru Waterfall - Sufiyanto Sufiyanto; Bagas Alfiansyah; Sari Yuniarti; Laksni Sedyowati; Djoko Andrijono (Universitas Muhammadiyah Magelang, 2023)
The PKKM policy implemented during the Covid-19 pandemic had an effect on the decrease in tourism. Due to these losses, Coban Waru Waterfall's natural tourism management had to deal with abandoned tourist attractions. After the pandemic, there is a need to reintroduce and attract visitors to the Coban Waru waterfall natural tourist attraction. Through digital promotion, this activity aims to raise public awareness of Coban Waru waterfall natural tourism. The method consists of the use of digital media promotion and training in content creation. As a result of this activity, a profile video and a leaflet titled